Introduction of Sustainability to Strategy Formulation at an Airport Operator Company - What are the Implications and how are they Perceived by the Stakeholders of Fraport AG? - Hoffmann, Andreas (2006)
In May 2005, Fraport, the operator of Frankfurt Airport, published a new vision which also incorporates a new focus on sustainable value development with respect to its employees and its environment. The focus of this work is on how this approach is put into practise and what this approach means to Fraport's stakeholders. It relates the company's approach to theory found in relevant literature. It also points out opportunities to improve the perception of the strategy. Sustainable strategy theory is compared with Fraport's approach to sustainable strategy. By interviews, document review and a survey, the conception of Fraport's strategy as well as the stakeholders' perception of the company's sustainability approach were examined. Interviews were conducted with spokespersons of the Strategy department at Fraport. This was put into perspective by a survey that tries to examine the perception of employees. This research assesses Fraport's commitment to its chosen strategy and also identifies areas for improvement by means of the interviews. The dissertation concludes with some recommendations of what could be improved to further establish the strategy of sustainability in the company's culture.